Cock rings, masturbation sleeves, and pulsating vibrators : contesting and reproducing heteronormativity via sex toy parties in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Sociology at Massey University, Manawatū, New Zealand - Smith, Janelle (Massey University, 2024)
Pure Romance is a US-based sex product retailer that operates commercial sex toy parties in four countries, including my hometown and research site, Palmerston North, Aotearoa New Zealand. This thesis critically examines and analyses Pure Romance’s female-only parties, product catalogue and website-based promotions, and female party attendees’ narrative responses to these. This was done to address the question of whether female-only sex toy parties reproduce or contest heteronormative and androcentric sexual scripts and discourses. My thesis analyses the company's promotion of lotions, potions, and sex toys using a theoretical framework comprising critical discourse analysis, sexual script theory, and vital materialism. Based on the promotional framing and agentic capacities of these products, a spectrum of conflicting and sometimes complementary sexual scripts and discourses is discovered. These overtly, and most prominently, reproduce the hegemony of heteronormative and androcentric sexual discourses through the equally conservative sexual scripts of the company promotions, facilitator narratives, and the narrative responses of party participants. However, this conservative reproduction was also significantly ameliorated by other, albeit less prominent, sexual scripts, which overtly promoted female masturbatory self-pleasure. Indeed, some female-centric scripts directly contested the phallocentric and/or penetrative ideals of heteronormative and androcentric sex by promoting clitoral-focused sexual activities. Furthermore, other scripts latently promoted homosexuality, both female and male, through the omission of any articulated rejection or contestation of such sexual practices. Overt contestation of hetero-and androcentric discursive values would involve the promotion of female solo masturbation/same-sex relationships as the preferred or idealised alternative, or indeed the primary and most celebrated goal of heterosexual encounters. However, evidence of this was lacking.
Keywords: 441010 Sociology of gender; 440102 Anthropology of gender and sexuality